Regulatory Effect of Adipose-Derived Mesenchymal Stem Cells and/ or Acitretin on Adam10 Gene in Alzheimer's Disease Rat Model - Abu Nasra, Noha O.; Elzayat, Emad M.; Dawood, Kamal M.; Hagag, Naglaa M.; Yehya, Manal M.; Hosney, Mohamed (Current Stem Cell Research & Therapy, 2022)
Background: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by progressive cognitive deterioration. All recent therapeutic strategies tend to inhibit the generation of the Aβ peptide. These approaches tend to mediate both α - and γ -secretases to undergo the nonamyloidogenic pathway. ADAM10 is the main α-secretase that cleaves APP, and it is regulated by the metabolic product of vitamin A (retinoic acid), which is being widely used recently in AD research as a target for treatment. Mesenchymal stem cells (MSCs) are also used recently as a promising regenerative therapy for AD. Objectives: The present study aimed to: (1) study the effect of MSCs with/without acitretin on the regulation of Adam10 gene expression in AlCl3-induced AD rat model, and (2) validate the hypothesis that AD is a time-dependent progressive disease that spreads spontaneously even after the stopping of exposure to AlCl3. Methods: The experimental work has been designed to include three successive phases; AlCl3 induction phase (I), AlCl3 withdrawal phase (W), and therapeutic phase (T). Forty-five male albino Wistar rats were randomly divided into 2 main groups: the control (C) group (15 rats) and AD group (30 rats). The therapeutic potential of MSCs with/without acitretin has been evaluated at behavioral, physiological, molecular, and histopathological levels. Results: Among the three therapeutic groups, combined administration of both MSC and acitretin showed the best compensatory effects on most of the measured parameters. Conclusion: The present study approved that AD is a time-dependent progressive disease which spreads spontaneously without more AlCl3 exposure.
Keywords: Alzheimer' s disease